OPTIMALISASI KREATIVITAS DAN KOLABORASI SISWA MELALUI PROJECT BASED LEARNING PADA PEMBELAJARAN GERAK BERIRAMA - Emayanti Anggraeni; Abu Istiyono; Mukharrar Fadjri; Ninik Septyani; Oktrin Ayulia Duwit (MAJU : Indonesian Journal of Community Empowerment, 2026)
This Student Creativity Program (PKM) activity aims to optimize students’ creativity and collaboration through the application of Project-Based Learning (PjBL) in teaching rhythmic movement within the Physical Education, Sports, and Health (PJOK) curriculum. The method used is a qualitative descriptive approach, with activities consisting of outreach, training, mentoring, implementation, and evaluation. The subjects of the activity were 30 junior high school (SMP) students selected using purposive sampling. The students were divided into small groups to collaboratively design and present rhythmic movement projects. Data collection techniques included observation, interviews, and documentation, while data analysis was conducted through data reduction, data presentation, and drawing conclusions. The results of the activity showed that the application of PjBL was able to enhance students’ creativity in creating movement variations, as well as improve their collaboration skills through more effective group work. Additionally, there was an increase in student engagement, self-confidence, and participation during the learning process. Students’ responses to this learning model were also very positive because it provided a more enjoyable and meaningful learning experience and could serve as an alternative innovative learning model in Physical Education (PJOK).